O’zbekiston tog’larida tarqalgan Juniperus L. Turkumi botanic tavsifi, vakillari va ahamiyati (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article is devoted to the botanical description of plants of the Juniperus L. genus, distributed in the mountains of Uzbekistan, their representatives and ecological significance. The Juniperus genus is one of the oldest and ecologically important groups of plants. These plants are mainly found in mountainous and foothill areas and are highly resistant, exhibiting drought and frost resistance. The article analyzes in detail the characteristics of plants belonging to the Juniperus genus, the biotopes in which they grow, and their ecological role. Juniperus representatives distributed in the Tien Shan, Fergana and Zarafshan mountains of Uzbekistan, especially such species as Juniperus communis and Juniperus turkestanica, are discussed. The article also considers the use of Juniperus plants in folk medicine and the construction industry, their economic and ecological significance, as well as their role in preserving the nature of Uzbekistan. The article emphasizes the need to increase the importance of Juniperus plants in ensuring ecological stability and managing natural resources.